2020
DOI: 10.1038/s41598-020-65339-9
|View full text |Cite
|
Sign up to set email alerts
|

Switching of Sox9 expression during musculoskeletal system development

Abstract: The musculoskeletal system, which comprises muscles, tendons, and bones, is an efficient tissue complex that coordinates body movement and maintains structural stability. The process of its construction into a single functional and complex organization is unclear. SRY-box containing gene 9 (Sox9) is expressed initially in pluripotent cells and subsequently in ectodermal, endodermal, and mesodermal derivatives. This study investigated how Sox9 controls the development of each component of the musculoskeletal sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 31 publications
(59 reference statements)
2
29
0
Order By: Relevance
“…Interestingly, recent embryonic development studies have reported that SOX9 is also essential for progenitor cells to differentiate into tenocytes (Sugimoto et al, 2012). In fact, consistent with our findings, Nagakura et al (Nagakura et al, 2020) showed that murine tenoprogenitor cells transiently express SOX9 in during development, and downregulate the same gene after differentiation to tenocytes in vivo.…”
Section: Discussionsupporting
confidence: 92%
“…Interestingly, recent embryonic development studies have reported that SOX9 is also essential for progenitor cells to differentiate into tenocytes (Sugimoto et al, 2012). In fact, consistent with our findings, Nagakura et al (Nagakura et al, 2020) showed that murine tenoprogenitor cells transiently express SOX9 in during development, and downregulate the same gene after differentiation to tenocytes in vivo.…”
Section: Discussionsupporting
confidence: 92%
“…The antero-inferior shift of the digastricus muscle due to formation of the intermediate tendon [ 11 ] seemed to drive separation of the SCM and trapezius muscles. Thus, bone formation at the muscle attachment can be affected by the mechanical load from the tendon [ 12 - 14 ]. However, the major driver underlying this separation seemed to be the developing clavicle.…”
Section: Discussionmentioning
confidence: 99%
“…PRS is linked to mutations in a Topologically Associated Domain (TAD, described below), containing a single protein coding gene, Sox9 ( Gordon et al, 2014 ). Sox9 plays a critical role during neural crest differentiation and craniofacial development ( Lee and Saint-Jeannet, 2011 ; Dash and Trainor, 2020 ; Nagakura et al, 2020 ) and enhancers near Sox9 have been implicated in craniofacial and chondrocyte development ( Liu and Lefebvre, 2015 ; Yao et al, 2015 ). PRS associated mutations are >1Mb from Sox9 and near a cluster of three enhancers the deletion of which leads to a 50% allele-specific decrease in Sox9 expression ( Long et al, 2020 ).…”
Section: Enhancersmentioning
confidence: 99%